Recovering from earthquakes : response, reconstruction, and impact mitigation in India - Patel, Shirish B.; Revi, Aromar (Routledge, 2010)
Earthquakes come without warming, and often cause massive devastation, resulting not only in the loss of property but also of lives. Many of the survivors suffer from intense and lasting psychological trauma. This book covers the experience of various earthquakes in India, and what has been learnt in the process of managing the aftermath